Review of food provision for athletes competing at the Tokyo 2020 Olympic and Paralympic Games - Pelly, F.; Dufour, A.; Tweedie, J.; Slater, G. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Teams that are competing at the Olympic and Paralympic Games (OPG) rely on food provided onsite at athletes` villages and at competition venues. Evidence has demonstrated that despite advance planning, food provided at these events does not adequately meet the needs of all athletes (1). Furthermore, restrictions have been placed on large scale catering with the advent of COVID-19 (2). The aim of this study was to review the proposed food provision for the Tokyo 2020 OPG in 2019 before COVID-19 and compare to the onsite delivery in 2021 during COVID-19. METHODS: A previously developed survey (1) was distributed to nine sport nutrition experts on two occasions during 2019 to review the on-paper menu for the Tokyo 2020 OPG. This was followed by an onsite review of food provision by 18 sports nutrition practitioners appointed to national teams during the delayed Tokyo OPG in 2021. RESULTS: Results demonstrated a significantly higher mean rating (1 = not suitable to 10 = very suitable) for the suitability of the main village menu on site (8.0) in comparison to the initial paper review (7.0; p=0.037). There was a negative correlation between sports nutrition practitioner experience (r = -0.479; P=0.009) and menu rating. Areas that were rated significantly better in terms of availability and acceptability on site than the 2019 paper review included pizza, fruit, yoghurt and food appropriate to make weight. Provision of breakfast cereal and muesli, vegetarian/vegan and snack/ sports foods were rated the worse by experts in 2021, with a rating of `poor` for the ability to request specific items on the menu. No significant differences were evident between the main village food and satellite villages and venues from the onsite 2021 review, however specific areas such as meeting food allergies, cultural diversity and vegetarian/ vegan items were rated as `poor` in locations outside the village. CONCLUSION: This is the first time that the food provision on site has been rated higher by experts than the proposed menu in advance of the event. Changes in food delivery due to COVID-19, including restricted numbers through the dining hall and fast turnover time of food, as well as a longer lead in time may have resulted in improved catering processes. Unlike in previous events (3), budgetary constraints, planning and procurement issues did not appear to be a limitation to appropriate food provision.